The Effect of Proportion and Drying Time on the Characteristics of Aloe Vera Skin (Aloe vera)-Pineapple (Ananas comosus) Tea - Jian Permani Ningsih; Rima Azara; Lukman Hudi (Universitas Muhammadiyah Sidoarjo, 2022)
Aloe vera skin tea is an herbal tea made from the waste of the aloe vera plant, it tastes bitter, and the unpleasant scent makes this tea less desirable. Therefore, other additives such as pineapple are needed which have a sweet and fresh taste and a strong scent so that they can mask the taste and scent of the aloe vera skin. In addition, pineapple also contains vitamin C which is efficacious as an antioxidant. Seeing the excellent benefits of the two, then the two can be combined into a product, namely aloe vera skin – pineapple tea which is expected to be able to add flavor and nutritional content. This study was conducted using a factorial Randomized Group Design (RAK) with the first factor, namely the ratio of aloe vera and pineapple skin consisting of 3 treatment levels, namely: (25%:75%, 50%:50%, and 75%:25%) and the second factor is the drying time (6, 8, and 10 hours). The data were analyzed using ANOVA then followed by the Honest Significant Difference (BNJ) test at a 5% level and a hedonic scale organoleptic test. The results showed that the highest values of water content parameters were 21,04%, vitamin C 5,28%, antioxidant activity 124,47 µg/ml, aroma organoleptic 3.63, and taste organoleptic 3.43.